A mechanistic review of pharmacological activities of homeopathic medicine licorice against neural diseases - Zulfugarova, Parvin; Zivari-Ghader, Tayebeh; Maharramova, Sevinj; Ahmadian, Elham; Eftekhari, Aziz; Khalilov, Rovshan; Turksoy, Vugar Ali; Rosić, Gvozden; Selakovic, Dragica (Frontiers in Neuroscience, 2023)
The use of medicinal plants has grown in popularity in recent decades because, as natural ingredients, they have fewer adverse effects and are more effective than synthetic alternatives. As a small perennial herb, Glycyrrhiza glabra L. (Licorice) has been investigated for its therapeutic efficacy against neural disorders mainly ischemic stroke as well as the neurodegenerative diseases such as dementia and Alzheimer's disease, and Parkinson’s disease which has been attributed to its HMGB inhibitory function, reactive oxygen scavenging and anti-inflammatory activity. The objective of current review is to review the evidence for the pharmacological effects of licorice and its vital active components on neurological disorders and the underlying signaling networks. We reviewed Papers published from 2000.1.1 up to 2th Jan 2023 in web of science, Google Scholar and PubMed data bases using key words including “Licorice”, “Glycyrrhiza glabra L.”, “Glycerrihizic acid”, “brain”, “neurodegenerative disease”, “Alzheimer’s”, and “Parkinson” were used to search in title/ abstracts. Licorice extract and/or its active components can be used safely in therapeutic doses for optimizing the management of a multiple neurodegenerative disorders, and hampering the extent of neural tissue injury and neurologic deficits subsequent to cerebrovascular accidents.